Um estudo sobre a “lógica do pensamento dedutivo” proposta por George Boole no contexto de algebrização da Lógica no século XIX - Janguas, Caio Cesar di Gesu (2019)
In this work, we discuss the elaboration of the "logic of deductive reasoning" proposed by George Boole (1815 - 1864), pointing to some aspects related to the process of "algebrization" of logic in order to approach its elaboration context in more detail. In order to do so, we carried out a study of the treatise Mathematical Analysis of Logic: Being in Essay of the Deductive Reasoning, published in 1847, on which we focused specific analyzes, considering epistemological and contextual aspects. On the one hand, this study sought to present Boole's reasons for "algebraizing the thought" and, consequently, the classical logic, which he considered to be the logic of deductive reasoning and human intellect and, on the other hand, to explain and comment on how he proceeded to algebraize logic, concluding that Boole's proposal consequently ended up shifting the Logic from the research field of Philosophy to that of Mathematics. The research presented here sought to present historical, mathematical and epistemological questions, based on an updated historiographic perspective, which can serve as a basis to produce bibliographical material for the reflection of the mathematical educator and the teacher